2021
DOI: 10.3390/polym13183079
|View full text |Cite
|
Sign up to set email alerts
|

Jawbones Scaffold Constructed by TGF-β1 and BMP-2 Loaded Chitosan Microsphere Combining with Alg/HA/ICol for Osteogenic-Induced Differentiation

Abstract: Bone scaffolds based on multi-components are the leading trend to address the multifaceted prerequisites to repair various bone defects. Chitosan is the most useable biopolymer, having excellent biological applications. Therefore, in the present study, the chitosan microsphere was prepared by the ion–gel method; transforming growth factor β (TGF-β1) and bone morphogenetic protein 2 (BMP-2) were loaded onto it and then combined with alginate/hyaluronic acid/collagen (Alg/HA/ICol) to construct a jawbones scaffol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…4,5 At present, there are many studies on the preparation of bioscaffold materials using the antibacterial activity of modified chitin or chitosan. [6][7][8][9] Chitosan's structure is similar to the glycosaminoglycans of bone tissue. [10][11][12][13] It has been found that adding polyethylene oxide (PEO) into CS solution could not only improve the electrospinning performance of CS, but also further enhance the hydrophilicity of CS-containing nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 At present, there are many studies on the preparation of bioscaffold materials using the antibacterial activity of modified chitin or chitosan. [6][7][8][9] Chitosan's structure is similar to the glycosaminoglycans of bone tissue. [10][11][12][13] It has been found that adding polyethylene oxide (PEO) into CS solution could not only improve the electrospinning performance of CS, but also further enhance the hydrophilicity of CS-containing nanofibers.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic materials such as β‐tricalcium phosphate/collagen‐I fibre scaffolds (Wang et al, 2021), hydrogel scaffolds (Kim et al, 2020), and PCL‐based nanofibrous composite scaffolds (Mansour et al, 2022) have also been employed to stimulate osteogenic differentiation of ADSCs. Bioactive factors such as growth factors, miRNAs, and exosomes have been harnessed to enhance the osteogenic differentiation of ADSCs (S. Yang et al, 2020; Tan et al, 2021). These strategies should be explored to improve periodontal tissue regeneration using DFAT cells in the future.…”
Section: Discussionmentioning
confidence: 99%
“…to enhance the osteogenic differentiation of ADSCs (S. Yang et al, 2020;Tan et al, 2021). These strategies should be explored to improve periodontal tissue regeneration using DFAT cells in the future.…”
Section: Histological Analysis Of Dfat Cell and Adsc Sheets For Repai...mentioning
confidence: 99%
“…The combined use of VEGF and rhBMP-2 can increase angiogenesis and blood supply, promote the formation of new bone and solve the problem of vertical bone regeneration in clinical work (Schorn et al, 2017). There is also TGF (Tan et al, 2021) similar to BMP synergistic osteogenesis. In addition to growth factors, some animal and plant active components such as BMP-2-related peptide P28 (Sun T. et al, 2018), amelogenin (EMD) (Miron et al, 2017) and Icariin (ICA) (Yin et al, 2017b) have also been applied in bone tissue engineering.…”
Section: Bioactive Barrier Membranesmentioning
confidence: 99%